Creativity and science in contemporary Argentine literature : between Romanticism and formalism - Page, Joanna (Latin American and Caribbean series, 2014)
With a burgeoning academic interest in Latin American science fiction and cyberfiction and in representations of science and technology in Latin American literature and cinema, this book adds new understanding to the growing body of interdisciplinary work on the relationship between literature and science in postmodern culture. Joanna Page examines how contemporary fiction and literary theory in Argentina consistently employ theories and models from mathematics and science to probe the nature of innovation and evolution in literature. Theories of incompleteness, uncertainty, and chaos are often.